The interface between the Mediation and Restorative Justice - Guerra, Gustavo Rabay (2016)
The present work starts stating the failure of the dominant paradigm of the penal system, retributive model, pointing to the emergence of restorative justice as a new paradigm of criminal justice, from the change in focus about the offender and in the rescue of victim’s role of conflict situations in the criminal orbit.In this sense, from the employment of mediation as restorative practice and identification of theoretical disagreements about the relationship between restorative justice and mediation, this article has the intention to investigate the existing interface between mediation and restorative justice in Brazil. Therefore, we start from the assumption that mediation and restorative justice are institutes with different origins and trajectories that at some moments have common destinations, presenting an intersection relationship when mediation is used in criminal matters as restorative practice.Thus, the research has as main aim to analyze similarities and differences between mediation and restorative justice in the Brazilian practice. From this perspective, we intend to make use of a comparative approach in the analysis of the institutes, to identify their origins and trajectories